Associated factors between the state of anxiety and a specific gymnastics skill with environmental variations - Barreto, Patrícia Marques [UNESP]; de Moraes, Mayra Grava [UNESP]; Zanini, Gabriel de Souza [UNESP]; Neiva, Cassiano Merussi [UNESP]; Terra, Gerusa Dias Siqueira Vilela; Filho, Dalton Müller Pessôa [UNESP]; Maffei, Willer Soares [UNESP]; Verardi, Carlos Eduardo Lopes [UNESP] (My University, 2016)
The present study had with goals to analyze the anxiety state and its relationship with the implementation of a specific skill of Gymnastics, held in different environments. The sample of the study consisted of 11 athletes of Gymnastics, female, representatives from the city of Bauru (Brazil). The athletes responded prefacing each evaluation to the Competitive State Anxiety Inventory-2 (CSAI-II) instrument that aims to measure the anxiety state. The results show that on the ground, considered the most secure environment, the gymnasts have demonstrated higher self-trust (27.27 ± 4.95) when compared with the low beam (26.36 ± 5.66) and with the high beam (25.27 ± 4.24) which presented the lowest result for self-trust.
Keywords: Anxiety State; Environmental variation; Gymnastics